2004
DOI: 10.3928/1081-597x-20041101-05
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Need for Enhancement After Laser in situ Keratomileusis

Abstract: PURPOSE: To confirm that enhancements after primary laser in situ keratomileusis (LASIK) are effective in dealing with residual refractive errors, and to determine if any variables prior to or during the primary LASIK procedure predisposed eyes to require subsequent enhancement. METHODS: A retrospective study of eyes undergoing primary LASIK with the VISX S2 or S3 laser and Hansatome microkeratome between January 1, 2000 and January 1, 2002 was done. Of the 393 eyes of 207 patients, 58 eyes (14%) und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Some reports have found that age is a factor, with younger patients having better outcomes, but other studies have not found an association. 9,19,20 In addition, studies of the possible benefi t of femtosecond-created LASIK fl aps have shown both similar and improved outcomes compared to mechanical keratome-created fl aps. 4,[21][22][23][24] Given these mixed results, it is not known whether patients who did not attend the 1-month examination would have collectively done better, worse, or the same as the cohort who attended the 1-month examination.…”
Section: Snellen Linesmentioning
confidence: 99%
“…Some reports have found that age is a factor, with younger patients having better outcomes, but other studies have not found an association. 9,19,20 In addition, studies of the possible benefi t of femtosecond-created LASIK fl aps have shown both similar and improved outcomes compared to mechanical keratome-created fl aps. 4,[21][22][23][24] Given these mixed results, it is not known whether patients who did not attend the 1-month examination would have collectively done better, worse, or the same as the cohort who attended the 1-month examination.…”
Section: Snellen Linesmentioning
confidence: 99%
“…In a young myopic patient with low to moderate myopia, regression can be avoided to a good extent and safely by using a post lasik aim of refraction of +1.0 D. From this study it is obvious that this safe margin of hypermetropia (SMH) considered safe because it is easily overcomed by accommodation so that doesn't impair UCVA, not cause significant eyestrain (asthenopia), play a good role in decreasing regression and preventing shift of refraction to myopic side. This simple maneuver of choosing safe margin of hypermetropia (SMH) can help dramatically to eliminate the need to enhancement procedure (12)(13)(14) and help to reach a good level of patient trust and satisfaction.…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports [2,5,36] indicated that older-aged patients are more likely to develop regression or require retreatment, as was found in the multivariate analysis in our study. One explanation is that surgeons are careful to undercorrect with myopic presbyopia with patients who are around 40 years of age, while they tend to overcorrect for young patients [41]. The second explanation is that the lenses of older patients might develop lenticular sclerosis with a myopic shift.…”
Section: Agementioning
confidence: 99%